2018
DOI: 10.1037/rel0000168
|View full text |Cite
|
Sign up to set email alerts
|

How does religiosity enhance psychological well-being? Roles of self-efficacy and perceived social support.

Abstract: It is known that religiosity is a positive correlate of well-being among adolescents and emerging adults. The current study extends this focus by assessing the roles of self-efficacy and perceived social support, which are presumed to explain the association of religiosity with psychological well-being (PWB). Participants were 331 adolescents and emerging adults (mean age = 21.67 years, SD = 3.92, range = 19–24, 68% male). In addition to correlation analyses, multimediation regression models were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 39 publications
(64 reference statements)
4
25
0
6
Order By: Relevance
“…Smith (2003) also claimed that religiosity exerts its beneficial effects on well-being through moral, psychological, and social factors. Explaining the religiosity-well-being link by religious or spiritual factors has been known as the nonreductionist approach, whereas explaining it by the nonreligious factors has been known as the reductionist approach (Fatima et al 2018). Religions 2020, 11, 149 3 of 14 We expected that r/s struggle would affect psychological well-being both by religious and nonreligious factors.…”
Section: Indirect Relations Between R/s Struggle and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith (2003) also claimed that religiosity exerts its beneficial effects on well-being through moral, psychological, and social factors. Explaining the religiosity-well-being link by religious or spiritual factors has been known as the nonreductionist approach, whereas explaining it by the nonreligious factors has been known as the reductionist approach (Fatima et al 2018). Religions 2020, 11, 149 3 of 14 We expected that r/s struggle would affect psychological well-being both by religious and nonreligious factors.…”
Section: Indirect Relations Between R/s Struggle and Well-beingmentioning
confidence: 99%
“…Religion is a source of support and consolation for many people as well as a predictor of mental health and personal adjustment (Fatima et al 2018;Koenig et al 2012;Park and Slattery 2013). A vast majority of research has confirmed negative correlations between religiosity and depression and anxiety (Park and Slattery 2013) and positive correlations between religiosity and the sense of happiness, well-being, and satisfaction with life (Bradshaw and Kent 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found that protective factors such as social support were important in decreasing the impact identity crisis had on mental health vulnerabilities. This relates to the aforementioned research surrounding social support and religious involvement (Debnam, Holt, Clark, Roth & Southward, 2013;Fatima, Sharif & Khalid, 2018) and expands to other research that emphasises the highly protective role social support has for mental health diagnoses (see Gariepy, Honkaniemi & Quesnel-Vallee, 2016). Importantly, the identity and social support implications can be viewed positively as they are concepts which can be modified and used as a basis for intervention.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, belief may form a crucial social currency outside of any meta-physical claims on reality (Williams, 2019). The communal nature of religious activities, such as those based in a place of worship, increases the availability of social interactions and creates a sense of belonging between like-minded people (Debnam, Holt, Clark, Roth & Southward, 2013;Fatima, Sharif & Khalid, 2018), and can even hold together the foundational culture of a country (Abdulla, 2018). Loneliness from changing one's belief and leaving this broad cultural and social network may increase risk to various vulnerabilities, psychological distress, and even psychiatric disorders (see Mushtaq, Shoib, Shah & Mushtaq, 2014), especially when coupled with potential migration vulnerability (Kirkbride et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, happiness does not just mean not to be sick but includes higher levels that affect both emotion and cognition. 4 Happiness is one of the factors influencing psychological wellbeing, so that happiness means positive feeling, feeling of satisfaction and minimal negative feeling, and these three factors considered as three critical factors in psychological well-being. 5 In addition, optimistic people show more effective coping behaviors, better and more valuable social relationships, higher flexibility, and more mental and physical well-being than pessimistic people.…”
Section: Introductionmentioning
confidence: 99%